Overload training at vVO2max does not alter performance at vVO2max - Billat, V. L.; Petit, B.; Koralsztein, J. P.; Fletcher, B. (Medicine & Science in Sports & Exercise, 1997)
This study assessed the value of increasing specific training volume on performance. The influence of a defined increase in training volume (threefold) at the velocity associated with VO2max on performance and heart rate was examined. Ss (N = 8) participated in four weeks of normal training with one session per week at vVO2max. The specific training session consisted of five sets of repetitions alternating running at vVO2max and 60%vVO2max (a fast-slow alternation). Intensified training consisted of running the alternating sets program three sessions per week. It was found that normal training increased the velocity associated with VO2max as a result of improved running economy. VO2max, lactate threshold, time to exhaustion at VO2max, or distance run at VO2max did not change. Heart rate decreased significantly. The intensified training produced no new changes. The increased overload was of no benefit to performance or physiological function. Implication: There is a certain level of stimulation caused by specific training stimuli that produce adaptations. Increasing the volume of that stimulation past an optimal point will not result in any further performance or physiological gains. This finding is in conflict with common practices of increasing training volumes of any intensity, almost without limit, in the belief that extra benefits will accrue. This produces a difficult challenge for coaches, to hold back on the number of specific intense training sessions that are required of athletes rather than subjecting them to excessive unproductive training.